How does corporate social responsibility affect innovative work behaviour? - Viet Quoc Cao (Global Business & Finance Review (GBFR), 2023)
Purpose: This research examines the effect of perceived corporate social responsibility on the employee-company relationship (organisational trust, organisational identification) and employees' future well-being and participation in innovative work practices. Design/methodology/approach: This study used a quantitative research approach by PLS-SEM analysis with a sample size of 400. The respondents are employees working for four distinct textile garment manufacturing enterprises in Vietnam. Findings: Our study found that corporate social responsibility directly impacts organisational trust, identification, well-being, and innovative work practices, and innovative work behaviours are directly related to organisational trust, employee well-being, and identification. Research limitations/implications: The study focuses on workers who have a basic understanding of corporate social responsibility. Consequently, the scope of research in diverse industries throughout the country's regions and cities must be expanded. Given the constraints, future studies should be broadened and conducted in greater detail. Each profession should concentrate its efforts on a broader range of survey subjects, such as office workers, employees, and consumers. Originality/value: Employee well-being is linked to innovative work behaviour, and the stronger the company's identity, the more likely people will be to be creative at work. The author found that people who work for a company that has a good sense of itself are more likely to be creative at work. The study shows that when employees are happy, they are more likely to work in new and innovative ways.
Keywords: 650; Innovative work behaviours; Organisational trust; Organisational identification; Well-being; Corporate social responsibility